Reseña de: Aldhouse-Green, Miranda: Sacred Britannia. The Gods and Rituals of Roman Britain - Perea Yébenes, Sabino (Espacio Tiempo y Forma. Serie II, Historia Antigua, 2020)
Reseña de: Aldhouse-Green, Miranda: Sacred Britannia. The Gods and Rituals of Roman Britain, London, Thames & Hudson, 2018, 256 pp., ISBN: 978-0-500-25222-2.